DESAIN KONSTRUKSI ALAT PENDINGIN PORTABEL DI SEPEDA MOTOR - Sopian, Yusuf; Rahmat, Mamat; Edi, Sutoyo (UNIVERSITAS IBN KHALDUN BOGOR, 2021)
The number of motorbike riders who modify their motorbikes uses a box, giving rise to the idea of modifying the box as a beverage cooler box. Modification of the box into a beverage cooler box affects the structure of the box, so it requires a bracket that matches the box. This study aims to determine the bracket strength when receiving loads 65.70 N. Obtain the value of the comparison of structural strength between theoretical calculations and CAD software simulation. Research methodology in this research method, researchers use quantitative methods. The things done in this research methodology, designing the design of a tool using CAD software, making a construction design, calculating the strength of the main part of the bracket when given a load are then theoretically compared with the strength of the material when given a load in simulation. The results of this study are known, the force that occurs in the main part of the bracket is 65.70 N. The calculation is theoretical approach deflection value on the main part of the bracket is 0.017 mm, bending moment in the main part of the bracket is 1.971 N / m, and voltage value bending on the main part of the bracket is 3.89 MPa, while the safety factor according to theoretical calculations is 2.72 simulation results using CAD software, namely inventor 2016 by using simulation stress analysis, the load that occurs in the main bracket is 65.70 N, displacement simulation results the maximum value is located at 0.0014 mm and the minimum value is at 0 mm, the maximum value and maximum voltage location (Von Misses) is at 7.146 Mpa and the minimum number is 0 MPa, while the Safety Factor is at a maximum of 15.